Correlation between the promoter basal core and precore mutations and HBsAg quantification in French blood donors infected with hepatitis B virus. Issue 3 (29th August 2014) - Pivert, A.; Servant‐Delmas, A.; Lunel‐Fabiani, F.; Le Guillou‐Guillemette, H.; Laperche, S.; Ducancelle, A.
<x xml:space="preserve">Abstract</x> Hepatitis B virus (HBV) basal core promoter (BCP) and precore (PC) mutations, HBV viral load and HBV surface antigen (HBsAg) quantitation were screened to assess correlations between these HBV markers in asymptomatic chronic hepatitis B carriers in France. From January 2006 to July 2007, 200 sera were collected from patients who were discovered to be HBsAg‐positive when they volunteered to give blood. Direct sequencing of precore/core gene was used to detect A1762T/G1764A mutations in the BCP and G1896A in the PC region. HBV viral load and HBsAg were quantified with two commercials assays. The prevalence of the BCP and PC mixed/mutants were 37% and 60% respectively (P = 0.0001). HBV DNA level and HBsAg titer were significantly lower in subjects harboring the mixed/mutant PC virus compared to those infected by the wild phenotype. No significant difference was observed in HBV viral loads of blood donors infected by wild or mixed/mutant BCP viruses. Mutant or mixed PC virus was associated with male gender, HBeAb‐positive status and HBV/D and HBV/E genotypes. BCP mutations were associated with age, and both HBV/A‐HBV/E genotypes.The genetic properties of HBV in this cohort showed that most of the blood donors had a negative HBeAg serological status and harbored the PC mutant phenotype in combination with low levels of both HBV DNA and HBsAg. As the study was conducted in healthy subjects who could be considered as asmptomatic carriers, these results suggest a possible protective effect of the G1896A mutation against severe liver lesions. J. Med. Virol. 87:529–535, 2015. © 2014 Wiley Periodicals, Inc.